2015
DOI: 10.1097/mao.0000000000000745
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Cohort Study on the Influence of Comorbidity on Soft Tissue Reactions, Revision Surgery, and Implant Loss in Bone-anchored Hearing Implants

Abstract: Retrospective analysis of comorbidity factors and clinical outcomes revealed risk factors for postoperative complications after BAHI surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 20 publications
2
26
2
Order By: Relevance
“…In addition to the large cohort investigated in this study, other strengths are the representative characteristics of our sample. The rates of implant loss and revision surgery were similar or slightly better compared with previous studies in our centre [ 7 , 20 ] or according to other studies [ 8 , 13 ]. In addition, no differences in baseline characteristics between both groups were noticed.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition to the large cohort investigated in this study, other strengths are the representative characteristics of our sample. The rates of implant loss and revision surgery were similar or slightly better compared with previous studies in our centre [ 7 , 20 ] or according to other studies [ 8 , 13 ]. In addition, no differences in baseline characteristics between both groups were noticed.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, the background characteristics mental retardation, dermatological disease and diabetes mellitus were registered, because recent studies focus on identification of these comorbidities as possible risk factors in the context of soft tissue reactions after BAHI surgery [ 7 , 18 20 ]. If there were no notes for these conditions in the medical chart or any correspondence within the chart of the patient, this comorbidity factor was considered absent.…”
Section: Methodsmentioning
confidence: 99%
“…Smoking, BMI and diabetes have all been postulated as factors for softtissue reactions or implant loss in BAHS and dental studies. [34][35][36] Recently, Sayardoust et al showed that smoking is associated with different gene profiles post-surgery for dental implants. 37 Here, we observed that, with intact skin, no gene expression differences were observed.…”
Section: Clinical Parametersmentioning
confidence: 99%
“…Finally, the background characteristics gender, body mass index, diabetes mellitus, mental retardation, smoking and cardiovascular comorbidity were registered, following recent studies focusing on identification of these comorbidities as (potential) risk factor for soft tissue reactions or implant loss [8, 3034]. In addition, some characteristics may be associated with skin flap necrosis or impaired wound healing [2628].…”
Section: Methodsmentioning
confidence: 99%